INTEGRAL INVOLVING ALEPH-FUNCTION AND THE GENERALIZED INCOMPLETE HYPERGEOMETRIC FUNCTION - (:unkn) unknown (TURKIC WORLD MATHEMATICAL SOC, 2020)
The aim of this paper is to establish a general definite integrals involving product of the Aleph function and generalized incomplete hypergeometric function with general arguments. Being unified and general in nature, this integral yield a number of known and new results as special cases. For the sake of illustration, several corollaries are also recorded here as special case of our main results.
Keywords: Aleph-function; I-function; H-function; generalized incomplete hypergeometric function; FORMULAS